AC power supply circuit architecture for a miniaturised retinal prosthesis device. Issue 10 (16th September 2021) - Mori, Yasuto; Chia‐Chi, Chang; Endo, Hiroki; Hata, Maho; Shodo, Kenzo; Terasawa, Yasuo; Noda, Toshihiko; Tokuda, Takashi; Haruta, Makito; Tashiro, Hiroyuki; Sasagawa, Kiyotaka; Ohta, Jun
Abstract: This study proposes an alternating current (AC)‐driven retinal prosthesis device using an implantable CMOS‐LSI chip that can control multiple electrodes. The proposed device uses AC power with the electrical grounds of the main and stimulation units separated to reduce the possibility of current leakage and to improve safety. The stimulation unit implanted in the eye cannot include large capacitor chips for ground separation. To solve this problem, large capacitor chips are mounted on the implantable control unit that supplies power, not on the stimulating device, and a cooperative mode of operation is devised. In this way, it is realised that a circuit configuration that achieves both miniaturisation and improved power supply efficiency. This study verifies the functionality of the proposed circuit. The results suggest that power supply and stimulation operations are possible through coupling capacitors. In addition, this stimulation operation can be performed continuously.